Exploring Missing Learning Phenomenon in Preschool Settings During Covid-19 Pandemic: Teachers’ Perspectives - Mazlan, Nurul Hijja; Adnan, Wardatul Hayat; Ayub, Suffian Hadi; Zeki, Mohd Zaidi (Universiti Utara Malaysia Press, 2024)
Purpose –This study aims to explore the missing learning phenomenon due to school closures during the COVID-19 pandemic in preschool settings from teachers’ perspectives in Selangor, Malaysia. Related studies have shown that missing learning phenomena from different settings leads to delayed literacy development and raises the risk of dropping out among children. There is a lack of in-depth documentation on the missing learning phenomenon among preschoolers exploring the socioecology of preschool settings in a local context.